Formal specification of system functions - Spanfelner, Bernd; Leuxner, Christian; Sitou, Wassiou (2009 ICSE Workshop on Modeling in Software Engineering, 2009)
Today's software systems tend more and more to comprise a multitude of different, often interfering functionalities. Especially in the case of embedded systems with their high requirements on safety this imposes additional risks for unwanted system behavior. Use cases are a common way to describe system functionalities in very early phases of the system design. Systematically translating these use cases into formal models in terms of system functions or services, respectively, constitutes a logical next step resulting in formal, service-oriented models. These models may facilitate validation activities, but are not efficient for formal verification. In this paper we propose an algebraic approach to specifying system functions as services. The proposed approach allows for model restructuring and transformation heading towards sufficing both requirements: intuitive validation and more efficient formal verification.